Pengaruh earning per share, profitabilitas, leverage dan ukuran perusahaan terhadap nilai perusahaan sektor keuangan yang terdaftar di BEI tahun 2015-2021 - Lestari, Dyah Lina; Hidayati, Amalia Nuril; Habib, Muhammad Alhada Fuadilah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Currently, investment is one of the fields of interest to the public. This investment activity is very beneficial both for companies that need business capital, as well as for potential investors. Prospective investors will use the value of the company as one of the guidelines in determining the company to invest in. Therefore, the company will maximize its financial performance to make the value of the company batter. The purpose of this study is to examine and analyze the effect of eamings per share, profitability, leverage and firm size on firm value in financial sector companies listed on the Indonesia Stock Exchange in 2015-2021. The population of this study ware 94 companies listed in the IDX financial sector, with a sample of 5 companies which ware taken through purposive sampling technique. The research data is taken from the annual report of the company’s official website for 2015-2021. This research uses a quantitative approach with associative type. The data analysis technique used panel data regression. Based on the Fixed Effect Model (FEM) test, the results show that earnings per share, profitability, leverage, and firm size have a significant positive effect on firm value. Based on the findings of this study, companies need to strive to increase earnings per share, profitability, leverage, and company size so that the value of the company increases, so that many potential investors are interested in investing in their company.